Volatile fatty acids production from municipal waste streams and use as a carbon source for denitrification: The journey towards full-scale application and revealing key microbial players. (April 2023) - Owusu-Agyeman, I.; Bedaso, B.; Laumeyer, C.; Pan, C.; Malovanyy, A.; Baresel, C.; Plaza, E.; Cetecioglu, Z.
Abstract: Volatile fatty acids (VFAs) production is attracting interest as a sustainable approach to maximize resource recovery from organic wastes. This study explored the interlink between long-term system resilience of VFA production from primary sludge (PS) and external organic waste (OW) without pH control and the microbial community dynamics as well as the effect of substrate variability. The study elucidated the practicality of using VFA-rich effluent as a carbon source for wastewater denitrification. A 15 L bench-scale semi-continuous reactor was operated for 315 days with a feed of 70% v/v PS and 30% v/v OW and scaled up to a 2 m 3 pilot-scale continuous reactor operated for 264 days. In the bench-scale study, the system was resilient with VFA production of up to 24, 700 ± 400 mg COD/L and a yield of 506 ± 25 mg COD/g VSfed . The VFA composition was dominated by caproic acid up to 62% w/w. In the pilot-scale reactor, substrate variability influenced VFA production with a concentration of up to 21, 500 ± 500 mg COD/L. The system was shown to be economically viable. The microbial community was dominated by Lachnospiraceae, Streptococcaceae and Comamonadaceae . The relative abundance of Lachnospiraceae gave a strong positive statistical correlation with caproic acid concentrations. The VFA-rich effluent exhibited a higher specific denitrification rate than methanol and acetate. Moreover, a continuous denitrification experiment with real nitrified wastewater resulted in a high nitrate removal efficiency with a maximum of 98%. The study demonstrates the production of bio-based products from organic wastes as alternatives to fossil-based products. Graphical abstract: Image 1 Highlights: Long-term VFA production from waste without pH control is feasible and resilient. VFA composed mainly of caproic acid with a percentage of up to 62%. VFA-rich liquid is proven to be suitable for denitrification even in the long-term. Upscaling to a 2 m 3 reactor shows the system's robustness and economic viability. Lachnospiraceae dominated and positively correlated with caproic acid and total VFA.